Evaluation of Online Learning Implementation in the Middle of the Covid-19 Corona Virus Pandemic in Palangka Raya SMA Penjas Subjects - Jeff Agung Perdana; Indrianto Arif Ramadhana; Yosita Wisman; Uket uket (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to determine the implementation of the administrative activities of the Physical Education teacher learning program during the COVID-19 pandemic at the Watershed School (DAS). This research is descriptive research. This research was conducted at MI Mutiara Insan Palangka Raya. Data collection techniques used interview techniques, namely through direct question and answer with school residents, namely school principals and physical education teachers. The data analysis techniques in this study are as follows: (1) data reduction, (2) data presentation, (3) data verification and (4) drawing conclusions. Based on the results of the study, it can be seen that the implementation of PJOK learning at MI Mutiara Insan PalangkaRaya is still being carried out despite the COVID-19 pandemic. In its implementation there are slight differences, from the usual face-to-face meetings turning into online learning at home by utilizing technology to break the chain of the spread of COVID-19. The teacher also adjusts the learning implementation plan to current conditions and according to instructions from the local education office. In delivering the material, the teacher uses the whatsapp group application because it is easy to use so that learning can run effectively. On indicators of assessment or evaluation of learning, teachers can only make assessments from the cognitive (knowledge) domain, cannot make assessments from the affective (attitude) and psychomotor (skills) domains.